2019
DOI: 10.1002/bjs.11307
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of plain English and visual abstracts for disseminating surgical research via social media

Abstract: Background: Patients are increasingly taking an active role in the design and delivery of surgical research. Public communication of results should also be encouraged, but this is often limited to non-expert commentary. This study assessed the role of plain English abstracts disseminated via social media in engaging patients and clinicians in the communication of surgical research.Methods: A three-arm randomized controlled trial with crossover of two intervention arms was performed. Manuscripts accepted for pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 7 publications
1
46
0
Order By: Relevance
“…Prior studies showed significant positive effects of visual abstracts to increase engagement within specific academic fields [e.g., surgery (Ibrahim et al, 2017 ; Chapman et al, 2019 ), geriatrics (Lindquist and Ramirez-Zohfeld, 2019 )]. Research designs to test their impact include retrospective cross-sectional evaluation (Koo et al, 2019 ), as well as more rigorous randomized prospective approaches (Ibrahim et al, 2017 ; Chapman et al, 2019 ). In the landmark study testing visual abstracts, Ibrahim et al ( 2017 ) conducted a prospective case-control crossover study of Annals of Surgery publications (Ibrahim et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies showed significant positive effects of visual abstracts to increase engagement within specific academic fields [e.g., surgery (Ibrahim et al, 2017 ; Chapman et al, 2019 ), geriatrics (Lindquist and Ramirez-Zohfeld, 2019 )]. Research designs to test their impact include retrospective cross-sectional evaluation (Koo et al, 2019 ), as well as more rigorous randomized prospective approaches (Ibrahim et al, 2017 ; Chapman et al, 2019 ). In the landmark study testing visual abstracts, Ibrahim et al ( 2017 ) conducted a prospective case-control crossover study of Annals of Surgery publications (Ibrahim et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research suggests that sharing a traditional journal article on social media increases attention and downloads [ 66 ]. This can be facilitated in many ways, including discussing the study in a blog [ 66 ], posting short tweets, or sharing visual abstracts, images that summarize the main findings in a research paper [ 63 65 , 67 ]. The latter has shown to increase attention to the study results in an appealing way with increased distribution and downloads as a result [ 62 ].…”
Section: Return On Investment: Does Social Media Add To Science Commumentioning
confidence: 99%
“…Lastly, the visual abstract of the RCT of plain English and visual abstracts for disseminating surgical research via social media by Chapman et al 7 generated more than 6070 impressions and 139 interactions, supporting the importance of producing visual information to increase the reach of research outputs on social media.…”
mentioning
confidence: 92%